Дропшиппінг як інноваційна концепція ведення бізнесу в умовах трансформації ланцюгів постачання - Ковальський, В. С.; Kovalskyi , V. S.; Юденко, Є. В.; Yudenko, Ye. V.; Пушкар, О. І.; Pushkar , O. I. (Науковий вісник Міжнародного гуманітарного університету. Сер.: Економіка і менеджмент. - 2020. - Вип. 46. - С. 20-29, 2020)
Статтю присвячено дослідженню дропшиппінгу як інноваційної концепції ведення бізнесу в умовах трансформації ланцюгів постачання. У ході дослідження проаналізовано ключові бізнес-форми організації системи логістики в умовах цифрової економіки: власна логістика (інсорсинг), дропшиппінг та ван-стоп е-комерція (one stop e-commerce). Визначено сутність та специфічні особливостіор ганізації дропшиппінгу. Окреслено форми організації, переваги та недоліки дропшиппінгу як концепції ведення бізнесу. Розглянуто та деталізовано етапи реалізації товарів за моделлю дропшиппінгу та виділено моделі дропшиппінгу, що використовуються в бізнес-процесах електронної торгівлі. Обґрунтовано перспективи розвитку дропшиппінгу в Україні з урахуванням світових трендів та діджиталізації економіки.

The article is devoted to drop shipping as an innovative concept of business organization in the conditions of supply chain transformation. The relevance of the selected research issues is determined by the fact that in the conditions of rapid development of economic processes, the general vector of e-commerce development is aimed at deepening logistics and service specialization. The study found that the introduction of drop shipping provides businesses with new opportunities to expand their activities expand the distribution network, increase the number of consumers, which in general leads to increased efficiency of business processes. The study found that drop shipping is one of the most common models of economic activity in the Internet environment. Distribution and drop shipping rapid development due to a wide range of benefits that are achieved through the use of business models, including: low level of barriers to entry into the business, no need for initial capital for the purchase of goods and the need for warehouses, flexibility of the range, differentiation of suppliers (the possibility of concluding several contracts), the ability to save overhead costs (no costs for delivery and storage), etc. According to the results of the study, the forms of drop shipping were structured, which include: drop shipping on a one-page site, sales based on drop shipping in social networks, on bulletin boards, through online stores, collective shopping services, and pseudo-showrooms. The general theoretical scheme of drop shipping is developed and two models of drop shipping used in e-commerce business processes are defined: the model "Delivery with payment" and the model "Delivery with subscription". It is established that drop shipping has become widespread in the international e-commerce system today. The dominant trend in the development of drop shipping is the hierarchical development of the drop-shipping infrastructure, when the market is forming a circle of large drop shippers, which provide relevant services to small drop shippers. Trends and prospects for the development of drop shipping in Ukraine are identified, in particular: intensification of the development of Internet services based on cloud technologies, deepening of service specialization, accumulation of certain functions by outsourcing companies, centralization of ordering.

Статья посвящена исследованию дропшиппинга как инновационной концепции ведения бизнеса в условиях трансформации цепей поставок. В ходе исследования проанализированы ключевые бизнес-формы организации системы логистики в условиях цифровой экономики: собственная логистика (инсорсинг), дропшиппинг и ван-стоп е-коммерция (one stop e-commerce). Определены сущность и специфические особенности организации дропшиппинга. Определены формы организации, преимущества и недостатки дропшиппинга как концепции ведения бизнеса. Рассмотрены и детализированы этапы реализации товаров по модели дропшиппинга. Выделены модели дропшиппинга, используемые в бизнес-процессах электронной торговли. Обоснованы перспективы развития дропшиппинга в Украине с учетом мировых трендов и диджитализации экономики.
Dropshipping as an innovative concept of doing business in the conditions of supply chain transformation
Keywords: Інтернет-середовище; Internet environment; Интернет-среда; електронна торгівля; electronic commerce; электронная торговля; ланцюги постачання; supply chains; цепи поставки; дропшиппінг; dropshipping; дропшиппинг; прямі продажі; direct sales; прямые продажи; інсорсинг; insourcing; инсорсинг